2019
DOI: 10.1103/physrevlett.123.066403
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Chiral Magnetic Effect

Abstract: A single Weyl fermion, which is prohibited in static lattice systems by the Nielsen-Ninomiya theorem, is shown to be realized in a periodically driven three-dimensional lattice system with a topologically nontrivial Floquet unitary operator, manifesting the chiral magnetic effect. We give a topological classification of Floquet unitary operators in the Altland-Zirnbauer symmetry classes for all dimensions, and use it to predict that all gapless surface states of topological insulators and superconductors can e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 89 publications
(158 reference statements)
2
60
0
Order By: Relevance
“…Another potential avenue for future research is in the area of Floquet engineering [56]. In particular, it may be possible to use the Floquet-Magnus expansion to obtain an approximate description of the relaxation to steady state, as recently demonstrated for the Kapitza pendulum with friction [57].…”
Section: Resultsmentioning
confidence: 99%
“…Another potential avenue for future research is in the area of Floquet engineering [56]. In particular, it may be possible to use the Floquet-Magnus expansion to obtain an approximate description of the relaxation to steady state, as recently demonstrated for the Kapitza pendulum with friction [57].…”
Section: Resultsmentioning
confidence: 99%
“…A topological classification of Floquet operators was performed in Ref. 32. It was shown that the classification of Floquet operators in d spatial dimensions coincides with that of gapless surface states of static topological insulators/superconductors in d dimensions.…”
Section: Gapless Floquet Topological States: Topology Of U (K)mentioning
confidence: 99%
“…So far we have assumed that U (k, T ) = 1 N ×N . When U (k, T ) = 1 N ×N , we use the deformed evolution operator (32). Note that…”
Section: B Class Aiii In D =mentioning
confidence: 99%
“…Recently, topological phases in periodically driven systems (Floquet systems) have attracted much attention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A large number of approaches to realize Floquet topological phases have been theoretically proposed [2,4,5,11,13,14,17] and experiments have been carried out [6,8] to engineer Floquet systems with nontrivial topological phases.…”
Section: Introductionmentioning
confidence: 99%